2012
DOI: 10.14429/djlit.32.5.2655
|View full text |Cite
|
Sign up to set email alerts
|

Use of Web 2.0 Technology by Library Professionals: Study of Selected Engineering Colleges in Western Uttar Pradesh

Abstract: This paper reports on the awareness and usage analysis of Web 2.0 technologies by library professionals in library and in their personal life at their workplaces. The methodology for the proposed study is 'Survey Method' with the help of structured questionnaire. The sample respondents chosen for the study consists of librarians, deputy librarians, assistant librarians, and library assistants. Total 100 questionnaires were distributed (randomly) to the selected sample for the current year; 92 valid samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Figure 17 shows the icons of Web 2.0 tools added in the proposed system. These results were consistent with those of Tyagi (2012) who found that "a large number of respondents are aware of Web 2.0 tools and are inclined to use them." In contrast Bhardwaj and Madhusudhan (2016b) found that "majority of legal information resources i.e.…”
Section: Clustering Of Resultssupporting
confidence: 91%
“…Figure 17 shows the icons of Web 2.0 tools added in the proposed system. These results were consistent with those of Tyagi (2012) who found that "a large number of respondents are aware of Web 2.0 tools and are inclined to use them." In contrast Bhardwaj and Madhusudhan (2016b) found that "majority of legal information resources i.e.…”
Section: Clustering Of Resultssupporting
confidence: 91%
“…Modern ICT-based tools of knowledge creation, identification and sharing like Web discovery tools, blogs,Wikis, RSS feeds, social neworking and social bookmarking are being used by libraies in developed countries very commonly (Tripathi & Kumar (2010). It may be observed from the review of literaure that LIS professionals in India are aware of Web 2,0 and Social Networking Sites (SNS) and active on SNS to socialize and keep themselves up-to-date, find jobs, and acquire information about conferences and seminars in their respective fields (Bhardwaj, 2014;Tyagi, 2012), but their involvement at institutional level for promoting library services and communication with users seems uncommon, as emerged for the findings of present study.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the uncertainty of staff and the limited participation of users were obstacles to using these tools. Another recent study (Tyagi, 2012) was conducted among librarians and library professionals in Western Uttar Pradesh and showed that librarians' skills in Internet usage influence the adoption of social media. The researcher also emphasized the need for a comprehensive study to find out the factors which affect social media participation among librarians.…”
Section: Literature Reviewmentioning
confidence: 99%